Pemanfaatan Jagung Dalam Pembuatan Tepung Sebagai Alternatif Ketersediaan Komoditi Pangan Pada Rumah Makan Di Desa Sitinjo Kabupaten Dairi - Muhammad Rizal Sitepu (Tourism, Hospitality And Culture Insights Journal, 2022)
Corn flour is a fine grain that comes from crushed dry corn. Processing of corn into flour is recommended compared to other semi-finished products, because flour is more resistant to storage, easy to mix, can be enriched with nutrients (fortification), and is more practical and easy to use for further processing. This study aims to determine the quality of corn flour from several different processing processes. The research was carried out in Sitinjo Village, Dairi Regency, from April to May 2022. This study used corn as raw material for variety B 89, with 3 treatments of corn flour processing, namely: without soaking/milling shelled corn directly into flour (A); soaking in plain water overnight (B); and soaking in 1% tape yeast solution overnight (C). Observations were made on the nutritional content of corn flour (moisture content, ash content, protein content, fat content, crude fiber content, and carbohydrates), and economic analysis of corn flour from each processing process tested, then data analysis was carried out descriptively. The results showed that: corn flour made by soaking in 10% yeast solution (C), had a higher protein and coarse fiber content than treatments A (without soaking) and B (soaking in plain water). The process of making corn flour without soaking (A), gave the highest profit compared to the treatment of immersion in plain water (B) and immersion in 10% tape yeast solution (C), with an R/C ratio of 2.38.